Association Between Social Support and Self-Esteem in People with Schizophrenia - Umara Rauf, Uzma Ali (Pakistan Journal of Psychology, 2017)
The purpose of this study was to find out the predictive relationship between social support and self-esteem in diagnosed and under-treatment people with schizophrenia. On the basis of previous researches following hypothesis was formulated 1) Over all social support and its sub-domains would have predictive association with self-esteem in people with schizophrenia. A purposive sample of 52 persons diagnosed with schizophrenia age ranges 18 to 55 (mean age = 36.63, SD = 9.377) who belonged to different socioeconomic status was taken from different hospitals of Karachi-Pakistan. A self-developed demographic form, Multi-Dimensional Scale of Perceived Social Support, Urdu Version (Rizwan & Aftab, 2009) and Urdu Version of Rosenberg Self-esteem Scale by (Sardar, 1998) were used as measures. To evaluate the results, descriptive statistics and multiple regression analysis were computed. Results indicated that over all social support explained 23% variance in self-esteem of persons with schizophrenia while support from significant others, family and friends accounted for 25%, 05% and 07% variance in self-esteem respectively. Limitations, implications and avenues for future research are discussed.